Youngia kangdingensis is a new synonym of Youngia pilifera (Asteraceae, Crepidinae) - Liao, Shu-Yuan; Chen, You-Sheng (Phytotaxa, 2024)
Through our examination of specimens (including the type material) and fieldwork, Youngia kangdingensis (Asteraceae, Crepidinae) is considered to be conspecific with Youngia pilifera and is synonymized herein.